Model Pemberian Layanan Fisioterapi yang Berbeda Memberikan Kontribusi Terhadap Manfaat Kesehatan dalam Perspektif Islam - Azizah, Noor Rifatul; Ulfa, Ika Mardiatul; Tambunan, Lensi Natalia; Maulida, Maulida; Maulida, Sena (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2025)
Islam-based physiotherapy services are an innovative approach that integrates medical principles and spiritual values in health care. This study aimed to analyze the effectiveness of physiotherapy services that combine conventional methods with Islamic principles, such as prayer, religious support and sharia ethics, in improving patients' quality of life. The results showed that Islam-based physiotherapy services significantly contribute to patients' physical recovery and mental well-being, in line with the Maqashid Shariah concept that emphasizes the preservation of the soul (hifzh an-nafs) and body (hifzh al-badan). However, the implementation of these services faces several obstacles, including limited facilities, low public awareness, and challenges in aligning medical standards with Islamic values. Supporting factors such as the competence of health workers, advances in telehealth technology, and community acceptance of this holistic approach are important elements in the success of the program. This study emphasizes the importance of community education, cross-sector collaboration, and the development of sharia-based guidelines to improve the effectiveness and sustainability of Islamic physiotherapy services. With this approach, health services not only meet medical standards but also align with Islamic teachings, supporting the creation of a physically and spiritually healthy society.